2007
DOI: 10.1007/s00438-007-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

A transgressive segregation factor (RKN2) in Gossypium barbadense for nematode resistance clusters with gene rkn1 in G. hirsutum

Abstract: Host plant resistance is an important strategy for managing root-knot nematode (Meloidogyne incognita) in cotton (Gossypium L.). Here we report evidence for enhanced resistance in interspecific crosses resulting from transgressive segregation of clustered gene loci. Recently, a major gene, rkn1, on chromosome 11 for resistance to M. incognita in cv. Acala NemX was identified using an intraspecific G. hirsutum cross with susceptible cv. Acala SJ-2. Using interspecific crosses of Acala NemXxsusceptible G. barbad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…As a result of the difficulty in assessing the contributions of epistasis, epistasis was just assumed to be another major reason for transgression (Rieseberg et al 1999). Wang et al (2008) reported that epistasis was responsible for transgressive segregation in resistance to the root-knot nematode in cotton. In their study, a major gene, rkn1, on chromosome 11 for resistance to Meloidogyne incognita in cv.…”
Section: Introductionmentioning
confidence: 98%
“…As a result of the difficulty in assessing the contributions of epistasis, epistasis was just assumed to be another major reason for transgression (Rieseberg et al 1999). Wang et al (2008) reported that epistasis was responsible for transgressive segregation in resistance to the root-knot nematode in cotton. In their study, a major gene, rkn1, on chromosome 11 for resistance to Meloidogyne incognita in cv.…”
Section: Introductionmentioning
confidence: 98%
“…Breeding for optimal resistance must be based on selection of progeny with combinations of genes homozygous for resistance. However, a highly susceptible parent can contribute to nematode resistance via transgressive segregation [5]. These crosses can derive highly resistant lines, even when both parents have a susceptible phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…These crosses can derive highly resistant lines, even when both parents have a susceptible phenotype. Such transgressive segregants can be used as improved resistance sources in crop breeding [5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example of such a trait in cotton is resistance to the root knot nematode (Meloidogyne incognito) where resistance is quantified by destructive sampling of root galling or egg counts of progeny that must be grown under RKN infested conditions (Zhang . DNA markers have been discovered that are linked to resistance to RKN (Niu et al 2007;Wang et al 2008). In addition to cost savings, MAS is a powerful tool to disrupt negative associations that may cause yield drag from certain resistant genetic sources.…”
Section: Breeding Technologymentioning
confidence: 99%